Continuum of Care for Hepatitis C Virus Among Patients Diagnosed in the Emergency Department Setting. (16th February 2017) - Anderson, Erik S.; Galbraith, James W.; Deering, Laura J.; Pfeil, Sarah K.; Todorovic, Tamara; Rodgers, Joel B.; Forsythe, Jordan M.; Franco, Ricardo; Wang, Henry; Wang, N. Ewen; White, Douglas A. E.
Summary: Urban emergency departments (EDs) have a high prevalence of undiagnosed hepatitis C virus (HCV) infection. We find that patients identified with HCV infection in the ED can progress to treatment and cure with rates comparable to ambulatory care settings. Abstract: Background: Urban emergency departments (EDs) seem to be able to detect new hepatitis C virus (HCV) infections at a high rate, but it is unknown the extent to which individuals screened in the ED can progress to treatment and cure. We evaluate the HCV Continuum of Care for patients identified with HCV in 2 urban EDs, and consider the results in the context of outcomes from ambulatory screening venues where 2%–10% of chronically infected patients are treated. Methods: This is a multicenter, retrospective cohort study of 2 ED HCV screening programs. Patients who screened HCV antibody reactive between 1 May and 31 October 2014 were followed for up to 18 months. The main outcome was the absolute number and proportion of eligible patients who completed each stage of the HCV Continuum of Care. Results: A total of 3704 ED patients were estimated to have undiagnosed HCV infection, and screening identified 532 (14.4%) HCV antibody–reactive patients. Of the 532 HCV antibody–reactive patients, 435 completed viral load testing (82%), of whom 301 (69%) were chronically infected. Of the 301 chronically infected patients, 158 had follow-up arranged (52%), of whom 97 attended their appointment (61%). Of these 97, 24 began treatment (25%), and 19 of these 24 achieved sustained virological response (79%). Conclusions: Urban EDs serve patients with poor access to preventive care services who have a high prevalence of HCV infection. Because ED patients identified with HCV infection can progress to treatment and cure with rates comparable to ambulatory care settings, implementation of ED HCV screening should be expanded.